2011
DOI: 10.1001/archgenpsychiatry.2010.152
|View full text |Cite
|
Sign up to set email alerts
|

Family-Based Analysis of Genetic Variation Underlying Psychosis-Inducing Effects of Cannabis<subtitle>Sibling Analysis and Proband Follow-up</subtitle><alt-title>Genetic Variation Underlying Cannabis Effects</alt-title>

Abstract: Genetic variation in AKT1 may mediate both short-term as well as longer-term effects on psychosis expression associated with use of cannabis, possibly through a mechanism of cannabinoid-regulated AKT1/GSK-3 signaling downstream of the dopamine D(2) receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(118 citation statements)
references
References 58 publications
6
109
0
2
Order By: Relevance
“…Furthermore, convergent findings suggest that CNR1 signaling may be abnormal in patients with this brain disorder, even if the functional specificity of these anomalies is unclear (Dalton et al, 2011). Moreover, CNR1 has been inconsistently associated with diagnoses of schizophrenia (Chavarría-Siles et al, 2008;Seifert et al, 2007), and genetic variability and cannabis use appear to interact in conferring risk for psychosis (Caspi et al, 2005;van Winkel et al, 2011b, Di Forti et al, 2012. Interestingly, CNR1 signaling has been implicated in dopamine signaling (Bloomfield et al, 2014), which is centrally linked with schizophrenia (Weinberger et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, convergent findings suggest that CNR1 signaling may be abnormal in patients with this brain disorder, even if the functional specificity of these anomalies is unclear (Dalton et al, 2011). Moreover, CNR1 has been inconsistently associated with diagnoses of schizophrenia (Chavarría-Siles et al, 2008;Seifert et al, 2007), and genetic variability and cannabis use appear to interact in conferring risk for psychosis (Caspi et al, 2005;van Winkel et al, 2011b, Di Forti et al, 2012. Interestingly, CNR1 signaling has been implicated in dopamine signaling (Bloomfield et al, 2014), which is centrally linked with schizophrenia (Weinberger et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in a verbal working memory task, Jager et al (2006) [173] found significantly greater activity in the left superior parietal cortex in the cannabis using group despite there being no differences in task performance, which may be consistent with the idea of a compensatory recruitment effect. [166] found in abstinent cannabis users a reduced anterior cingulate activation using H2 15 O-PET during the performance of a modified Stroop test. However, they also reported a reduced dorsolateral prefrontal cortex activation and a greater activation in the hippocampus bilaterally [166].…”
Section: Memorymentioning
confidence: 99%
“…In a H2 15 O-PET study, Block et al (2002) [164] found that cannabis users performed verbal memory tasks more poorly than controls. This was associated with reduced activation in the prefrontal cortex and greater activation in the posterior cerebellum, as well as with an absence of lateralization of hippocampal activity.…”
Section: Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…The age (or developmental stage) at which individuals start using cannabis influences this association [135]. Further evidence suggests that geneenvironment interactions are likely implicated in the association between cannabis and psychosis [133,[136][137][138][139]. For example, the psychotomimetic effect of cannabis is much greater in siblings of patients with a psychotic disorder, who are at increased genetic risk to develop psychotic disorder than in controls [140].…”
Section: Drugs Of Abusementioning
confidence: 99%